Parameter optimisation research for hydraulic turbine regulating system based on CGABC algorithm. (28th March 2021) - Tan, Xiaoxia; Chen, Jing; Chen, Gonggui
Artificial bee colony (ABC) algorithm is regularly taken in the parameter optimisation of the hydraulic turbine regulating system (HTRS). The chaotic and global artificial bee colony (CGABC) algorithm is proposed to overcome the slow convergence speed and low convergence precision that existed in standard ABC algorithm. Among them, global optimal is used to enhance the global exploration ability, and chaos optimisation is adopted to increase the diversity of bee colony. The simulation results show that compared with fuzzy strategy, ZN, DE and ABC algorithm, the proposed CGABC algorithm significantly improves the dynamic transition process of HTRS. Simultaneously, the simulation experiment is carried out on HTRS with different governor parameters and controlled parameters when it is under the frequency and load disturbance condition. The results show that the dynamic characteristics and robustness is determined by the parameter selection, and the appropriate combination of parameters allows HTRS to achieve optimal dynamic performance and robustness.